An analysis of the contrasting fates of locust swarms on the plains of North America and East Asia - G. Yu; X. Ke; H. D. Shen; Y. F. Li (Biogeosciences, 2013)
Prior to ~1880 AD locust swarms periodically raged across both the North American Plains (NAP) and East Asian Plains (EAP). After this date, locust outbreaks almost never recurred on the NAP but have continued to cause problems on the EAP. The large quantities of pesticides used in the major agriculture regions of the NAP in the late 1870s have been suggested as a possible reason for the disappearance of locust outbreaks in this area. Extensive applications of modern, i.e. more effective, chemical pesticides were also used in the granary regions of the EAP in the 1950s in an effort to reduce pest outbreaks. However, locust swarms returned again in many areas of China in the 1960s. Therefore, locust extinction on the NAP still remains a puzzle. Frequent locust outbreaks on the EAP over the past 130 yr may offer clues to the key factors that control the disappearance of locust outbreaks on the NAP. This study analysed the climate extremes and monthly temperature–precipitation combinations for the NAP and EAP, and found that differences in the frequencies of these climate combinations resulted in the contrasting locust fates in the two regions: restricting locust outbreaks in the NAP but inducing such events in the EAP. Validation shows that severe EAP locust outbreak years were coincidental with extreme climate-combination years. Therefore, we suggest that changes in frequency, extremes and trends in climate can explain why the fate of locust outbreaks in the EAP was different from that in the NAP. The results also suggest that, with present global warming trends, precautionary measures should be taken to make sure other similar pest infestations do not occur in either region.